Sans Papiers The Social and Economic Lives of Young Undocumented Migrants - Block, Alice (Pluto Press, 2014)
Undocumented migration is a huge global phenomenon, yet little is known about the reality of life for those involved. Sans Papiers combines a contemporary account of the theoretical and policy debates with an in-depth exploration of the lived experiences of undocumented migrants in the UK from Zimbabwe, China, Brazil, Ukraine and Turkish Kurdistan. Built around their voices, the book provides the reader with a unique understanding of migratory processes, gendered experiences and migrant aspirations. Moving between the uniqueness of individual experience and the search for commonalities, the book explores the ambiguities and contradictions of being an undocumented migrant. With its insights into personal experiences alongside analysis of wider policy issues, Sans Papiers will have wide appeal for students, academics, policy-makers and practitioners.